Responses of Salmonella enterica Serotype Typhi to Hydrogen Peroxide - Thong, Kwai Lin; Chan, Kok Gan; Devi, Shamala (Faculty of Science, University of Malaya, 2003)
A strain of Salmonella enterica serotype Typhi (S. Typhi) used in this study can survive in high concentrations of hydrogen peroxide of up to 100mM. It could be adapted to grow in concentration of hydrogen peroxide of up to 250mM when the culture has been pre-treated with nonlethal concentration of hydrogen peroxide (60μ M). Adapted cells were found to be resistant to heat killing at 50Â°C. SDS-PAGE analysis showed that two outer membrane proteins of molecular weight of 45 and 68 kDa were synthesized when S. Typhi cells were challenged with 50mM hydrogen peroxide. Both of these OMPs were not present in untreated cell cultures. Immunoblotting experiments with sera from patients with a culture positive diagnosis of typhoid fever showed that these proteins were immunogenic.